ChemInform Abstract: Synthesis of Novel Pentacyclic Thiopyrano Indole‐Annulated Benzo‐δ‐sultone Derivatives via a Domino Knoevenagel‐hetero‐Diels—Alder Reaction in Water. Issue 36 (15th August 2013) - Moghaddam, Firouz Matloubi; Khodabakhshi, Mohammad Reza; Kiamehr, Mostafa; Ghahremannejad, Zahra
Abstract The formation of the heterocyclic skeleton proceeds in water without the need for any catalyst or additive with complete regioselectivity and moderate to good diastereoselectivity.